Pharmacogenetics and pharmacogenomics: expectations and ethical issues. - Spagnolo, A.G.; Minacori, R. (Medicina e Morale, 2002)
The pharmacogenetics has initially been defined as the study of the variability of individual answer to the medicine tied to personal and family genetics. During the last ten years, the term pharmacogenomics has subsequently sharpened such definition delineating with more precision the fields and the aims of this new scientific area. The objective is fascinating and important even more: to develop and to use new personalized pharmacological therapies, more effective and less harmful, using the discoveries on the human genome. From the development of this new application of the genetics a change will probably depend also the medical routine, with new diagnostic criterions and especially in the possibility to administer some personalized therapies. Besides the different technical-scientific issues that are solving yet, the genomics applied to the pharmacological research - that concerns for its field of interest the human genome, and therefore the human person and his/her aims - reachs new and optimal therapeutic solutions through the clinical search but also a wide ethical reflection in comparison to a plurality of elements at stake. On the other hand it is also necessary to consider that they are possible both therapeutic advantages and disadvantages ones for minority of population. Therefore it is fundamental that a wide and articulated reflection and suitable solutions are undertaken before the marketing of the pharmacogenetical tests that could cause discriminations among the patients. In the article, the Authors underline the ethical issues related to the basic search in pharmacogenetics, to the identification, to the collection and the patents of the personal data, to the applied search in pharmacogenetics, with the development of diagnostic devices and their use in the clinical experimentations, to the procedures for the maintenance of the biological samples and of the data and for the guardianship of the privacy, to the role of the Ethics Committees in the evaluation of the experimental protocols of pharmacogenetics, to the informed consent for the subjects of experimentation.